The volatility of green and non-green sovereign bonds on the emerging EU markets - Mercédesz Mészáros; Máté Csiki; Gábor Dávid Kiss (European Financial and Accounting Journal, 2023)
Green finance is becoming increasingly important today, affecting many areas of the economy. In this regard, the examination of green bond markets is becoming more and more important, as various financial shocks have also led to significant changes in the financial markets and economic policy processes. However, only a few of these new financial assets were issued on the emerging EU market, therefore the side effects of them have not yet been fully explored. In addition, the rise of green finance is only in its infancy in smaller economies, in various financial markets, which may be important to monitor in future investment decisions. The aim of our study was to examine the volatility properties of green sovereign bonds of European small open economies for the period between 2016 and 2021, where we analysed how the differences of these green sovereign bonds to conventional sovereign bonds changed over time. Also, we wanted to test whether there was a possibility of a conditional volatility premium for green government bonds. To answer our research questions, we calculated conditional volatilities, and the green premiums towards their standard forms using GARCH models. Our result suggested that the Polish and Hungarian green sovereign bonds have higher volatility than the traditional ones, which is the opposite of the German experience.
Keywords: C58; F30; G10; G15; 650; GARCH; Green Finance; Sovereign Bond Market